Les contestations sociales du développement touristique dans les Hautes-Pyrénées : le rendez-vous manqué de l’innovation territoriale ? - Sylvie Clarimont; Vincent Vlès (Revue de Géographie Alpine)
In the Pyrenees, the decentralised manner in which planning permission is awarded to projects might give the impression that the expansion of ski resorts is now more attuned to the concerns of local people, with potential conflicts handled more effectively than they were in the past. The reality is in fact quite different: The direct proximity of highly artificial spaces dedicated to winter sports with zones of exceptional environmental and natural importance continues to produce many conflicts; however, these receive relatively little media attention, but they have the potential to block development. Today’s anti-development associations are using new tools and methods, and their ability to counter proposed projects is undeniable. Presenting a resistance that is “solid, well-organised and backed up by legal expertise”, they use legal channels to campaign against projects they consider to be harmful, and they eschew mass demonstrations. This marks a clear break from previous approaches. Unlike the protest movements of the 1970s, these citizens’ associations remain pragmatic, non-hierarchical and local, led by ‘mountain folk’. Some local campaigns are ambiguous in nature and bring together a highly diverse array of stakeholders with interests in the local economy. Protest groups first and foremost, these associations rarely transcend their oppositional stance to propose real alternatives and become a force for territorial innovation.